Artificial intelligence-driven forest fire land susceptibility mapping: A remote sensing and machine learning approach - Xulong Duan; Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Aqil Tariq (Land Use Policy, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Synthesis and application of NiFe2O4/Nb2C-MXene composites for enhanced microbial fuel cell performance in wastewater treatment: Advancing sustainable bioelectricity generation - Muhammad Waseem Mumtaz; Haseeb Ashraf; Hamid Mukhtar; Memona Sadiqa; Uroosa Saeed; Waheed Miran; Tahir Iqbal; Aashir Waleed; Umer Rashid (Biomass and Bioenergy, 2026)

Rice husk-derived nanosilica alleviates aluminum accumulation and toxicity in Brassica napus by regulating cellular metabolism and antioxidant defense - Raheel Munir; Nazia Jan; Bahar Ali; Rana Muhammad Amir Gulzar; Muhammad Haseeb Javaid; Iqbal Hussain; Yinbo Gan (Environmental Research, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Titanium dioxide nanoparticles modulate soil bacterial communities to mitigate arsenic accumulation in contrasting maize varieties - Muhammad Ali Shah; Haseeb Ahmad; Shahid Ali; Kashif Khan; Rayyan Khan; Xi Zheng; Xun Bo Zhou (Applied Soil Ecology, 2026)

CRISPR-based gene editing for antimicrobial resistance control in human medicine - Abdullah Afzal Alvi; Muzzamil Hussain; Sadia Noureen; Zahid Abbas Malik; Sidra Zahoor; Areej Jamil; Muhammad Ali Mohsin; Asad Azeem; Haseeb Javaid; Zeshan Hassan (Archives of Microbiology, 2026)

A comprehensive review of innovative green hydrogen production technologies and catalysis developments - Saad Uddin Mahmud; Yew Heng Teoh; Heoy Geok How; Haseeb Yaqoob; Mohamad Yusof Idroas; Thanh Danh Le; Muhammad Ahmad Jamil; Hafiz Muhammad Ali; Muhammad Wakil Shahzad (Journal of Environmental Management, 2026)

Synergistic protection: Integrating in silico and in vivo evidence for Moringa oleifera flavonoids as potent Mitigators of Deltamethrin toxicity - Muhammad Sarfraz; Irfan Baboo; Zahid Farooq; Haseeb Khaliq; Valiollah Palangi (Research in Veterinary Science, 2026)

From climatic moderation to persistent hotspots: decadal insights into soil erosion risk from RUSLE–GIS modeling in the northwestern mountains of Pakistan - Khurrum Ahmad Khan; Syed Amer Mahmood; Muhammad Haseeb (CATENA, 2026)

Machine Learning and Deep Learning for Snowmelt Prediction: Long-Term Trends and Implications for Water Resource Management - Dawood Ahmad; Muhammad Haseeb (Water Resources Management, 2026)

Correction to: Spatio-temporal interactions of air pollution, vegetation health, and land surface temperature: Insights from multisensor satellite observations - Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Aqil Tariq; Nazih Y. Rebouh; Khadeijah Yahya Faqeih; Somayah Moshrif Alamri; Eman Rafi Alamery (Environment, Development and Sustainability, 2026)

Bacillus subtilis enhances maize yield by restricting cadmium translocation and modulating ion homeostasis - Haseeb Ahmad; Jiu Yang Mao; Rayyan Khan; Muhammad Ali Shah; Kashif Khan; Muhammad Asad Naseer; Shahid Ali; Rida Rashid; Rui He; Xun Bo Zhou (Journal of Environmental Sciences, 2026)

Spatio-temporal interactions of air pollution, vegetation health, and land surface temperature: Insights from multi-sensor satellite observations - Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Aqil Tariq; Nazih Y. Rebouh; Khadeijah Yahya Faqeih; Somayah Moshrif Alamri; Eman Rafi Alamery (Environment, Development and Sustainability, 2026)

Key metabolic and proteolytic pathways contributing to cadmium tolerance in soybean - Shahid Ali; Hao Yun Liang; Muhammad Ali Shah; Haseeb Ahmad; Yu Xin Chi; Kashif Khan; Xun Bo Zhou (Plant Science, 2026)

Genetic and epigenetic mechanisms underlying cadmium (Cd) stress responses in soybean cultivars - Shahid Ali; Ya Huang; Rayan Khan; Kashif Khan; Yu Xin Chi; Muhammad Ali Shah; Muhammad Asad Naseer; Haseeb Ahmad; Wen Jie Chen; Xun Bo Zhou (Plant Cell Reports, 2026)

Formulation Design of Glucuronoxylan-Based Stimuli-Responsive Microparticles for Zero-Order Drug Delivery - Saleha Babar; Fatima Akbar Sheikh; Syed Nasir Abbas Bukhari; Muhammad Tahir Haseeb; Arshad Ali; Nisar Ul Khaliq; Ranya Abdulrahman Alafar; Mohamed Abdelwahab Abdelgawad; Ameeduzzafar Zafar; Naveed Ahmad (Journal of Pharmaceutical Innovation, 2026)

Antimicrobial Peptides as Next-Generation Disinfectants: Tackling Biocide and Antimicrobial Resistance in Hospital Hygiene – A Narrative Review - Muhammad Umer Asghar; Noor Ul Ain; Muhammad Tariq; Arsalan Haseeb Zaidi (Probiotics and Antimicrobial Proteins, 2026)

Optimizing Phosphorus Use Efficiency and Fodder Yield of Pearl Millet: Two-Year Field Evaluation of Phosphorus-Solubilizing Bacteria with Inorganic Fertilizer Under Alkaline-Calcareous Soils - Abdul Majeed; Qasim Ali; Muhammad Haseeb Javaid; Muhammad Naveed; Mubshar Hussain (International Journal of Plant Production, 2026)

Efficient De Novo Assembly and Recovery of Microbial Genomes from Complex Metagenomes Using a Reduced Set of k-mers - Hajra Qayyum; Muhammad Faheem Raziq; Haseeb Manzoor; Syed Shujaat Ali Zaidi; Amjad Ali; Masood Ur Rehman Kayani (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Human versus machine: Can generative AI anticipate insect biological control outcomes? - Kris A.G. Wyckhuys; Komivi S. Akutse; Divina M. Amalin; Salah-Eddin Araj; Marie Joy B. Beltran; Ibtissem Ben Fekih; Paul-André Calatayud; Lizette Cicero; Marcellin C. Cokola; Yelitza C. Colmenarez; Kenza Dessauvages; Thomas Dubois; et al. (Computers and Electronics in Agriculture, 2026)

Fuel-flexible flat-tubular solid oxide fuel cell stack for high performance and durable operation - Muhammad Haseeb Hassan; Saeed Ur Rehman; Syeda Youmnah Batool; Amjad Hussain; Rak-Hyun Song; Tak-Hyoung Lim; Jong-Eun Hong; Dong-Woo Joh; Seok-Joo Park; Hye-Sung Kim; Seung-Bok Lee (Chemical Engineering Journal, 2026)

Long-term mangrove dynamics and safety in coastal areas: An emergency Remote Sensing-based analysis using Landsat and Sentinel-2 Data - Wenyang Xu; Muhammad Haseeb; Xiangtian Zheng; Zainab Tahir; Syed Amer Mahmood; Mona S. Ramadan; M. Abdullah-Al-Wadud; Aqil Tariq (Marine Pollution Bulletin, 2026)

Photocatalytic Degradation of Synozol Navy Blue Dye Using Ni-Ag Co-doped ZnO: Optimization, Mechanistic, Scavenging and Kinetics Studies - Zahid Mehmood; Muhammad Alamzeb; Tahseen Ghous; Sidra Rashid; Zulfiqar Ali; Muhammad Haseeb; Sabah Ansar; William N. Setzer (Journal of Fluorescence, 2025)

Unveiling the spectrum of vancomycin resistance in Staphylococcus aureus from Hospital-acquired urinary tract infections (HA-UTI) in cardiac patients - Muhammad Umer Asghar; Muhammad Tariq; Arsalan Haseeb Zaidi; Kabeer Haneef; Aisha Asghar; Noor Ul Ain (Molecular Biology Reports, 2025)

Heat stress-induced sterility in oilseed crops: a focus on Brassica napus - Muhammad Zeeshan Mola Bakhsh; Muhammad Ikram; Ahmad Ali; Haseeb ur Rehman (Molecular Biology Reports, 2025)

Biochar-Seaweed Fertilizer Blend: A Multifaceted Strategy for Mitigating Nitrous Oxide Emissions, Soil Rejuvenation, and Improving Rice Crop Performance - Muhammad Aamer; Huang Guoqin; Jiaen Zhang; Hui Wei; Fahd Rasul; Daolin Sun; Wenyun Huang; Shijie Liu; Abdul Haseeb; Tahani A. Y. Asseri; Mohamed Hashem (Journal of Soil Science and Plant Nutrition, 2025)

Retraction Note: Pharmacological support to anti-arthritic prospective of physostigmine: a new approach - Haseeb Ahsan; Ihtisham Haider; Muhammad Naveed Mushtaq; Muhammad Naeem Qaisar; Farwa Naqvi; Awais Asif (Inflammopharmacology, 2025)

From global challenges to specific solutions: climate change impacts on agriculture with a focus on sorghum through bibliometric analysis - Waqas Liaqat; Muhammad Tanveer Altaf; Muhammad Faheem Jan; Haseeb Ahmad; Ehtisham Hassan Khan; Celaleddin Barutçular; Gönül Cömertpay; Faheem Shehzad Baloch; Heba I. Mohamed (Cereal Research Communications, 2025)

Mitigating Fruit Drop Challenges: Unraveling the Role of Plant Growth Regulators and Micronutrients in Jujube (Ziziphus mauritiana L.) cvs. in the Cholistan Desert, Pakistan - Abdul Haseeb Ahmed; Rashad Qadri; Khalid Hussain; Muhammad Tahir Akram; Muhammad Azam; Muhammad Awais Ghani; Muhammad Mumtaz Khan; Muhammad Asif Rai; Basharat Ali; Abd El-Zaher M. A. Mustafa; Mohamed S Elshikh; Ghulam Murtaza; et al. (Applied Fruit Science, 2025)

Reimagining land use policies: Carbon trade-offs between urbanization and ecological restoration - Fei Shen; Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Aqil Tariq (Land Use Policy, 2025)

Impact of COVID-19 on the prevalence of multi-drug-resistant bacteria: a literature review and meta-analysis - Haseeb Ahmed; Zain Ul Abideen; Ammar Azmat; Muhammad Irfan; Salman Anjum; Afaf Dirie (Antonie van Leeuwenhoek, 2025)

Towards greening smart cities: Navigating net zero carbon in construction by 2050 through sustainable practices, innovation climate, and management support - Muhammad Javid Nawaz; Aymen Sajjad; Abdul Haseeb Tahir; Muhammad Adnan; Muhammad Umer; Huaming Song (Sustainable Cities and Society, 2025)

Corrigendum to “Elucidating arsenic-induced stress responses in maize genotypes: Unravelling biochemical, physiological, and nutrient homeostasis for enhanced resilience” [Sci. Total Environ. 998 (2025) 180305] - Muhammad Ali Shah; Jiu Yang Mao; Rayyan Khan; Haseeb Ahmad; Shahid Ali; Kashif Khan; Muhammad Asad Naseer; Rida Rashid; Li Yang; Xun Bo Zhou (Science of The Total Environment, 2025)

Elucidating arsenic-induced stress responses in maize genotypes: Unravelling biochemical, physiological, and nutrient homeostasis for enhanced resilience - Muhammad Ali Shah; Jiu Yang Mao; Rayyan Khan; Haseeb Ahmad; Shahid Ali; Kashif Khan; Muhammad Asad Naseer; Rida Rashid; Li Yang; Xun Bo Zhou (Science of The Total Environment, 2025)

Analyzing and predicting land use and land cover dynamics using multispectral high-resolution imagery and hybrid CA-Markov modeling - Xulong Duan; Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Aqil Tariq (Land Use Policy, 2025)

Non-linear complementarity model including large displacements and strain rate effects for RC beams under impact - Muhammad Anas; Haseeb Ahmed; Azam Khan; Mudassir Arshad; Moiz Tariq (Engineering Structures, 2025)

Propolis enhanced sodium alginate hydrogel enriched with copper doped mesoporous bioactive glass nanoparticles for advanced burn care applications - Aqsa Aizaz; Muhammad Haseeb Nawaz; Muhammad Sameet Ismat; Md Abdur Rashid; Muhammad Atiq Ur Rehman (Biotechnology Letters, 2025)

Quantitative Analysis of Pesticide Residues in Guava (Psidium guajava L.) Fruit by Using High Performance Liquid Chromatography - Rashad Qadri; Abdul Haseeb Ahmed; Muhammad Umair Ashraf; Muhammad Tahir Akram; Khalid Hussain; Muhammad Azam; Muhammad Imran Khan; Muhammad Mumtaz Khan (Applied Fruit Science, 2025)

Evaluating the Impact of Triacontanol on Physiological, Enzymatic and Biochemical Responses of Psidium Guajava L. Under Salinity Stress - Khalid Hussain; Rashad Qadri; Rashid Iqbal Khan; Abdul Haseeb Ahmed; Muhammad Azam; Muhammad Tahir Akram; Muhammad Imran Khan; Aneeqa Arshad; Swati Shrestha (Applied Fruit Science, 2025)

Variation in Ectotherm Thermal Tolerances With Elevation and Temperature Across Biological Scales - Imran Khaliq; Edward Lavender; Haseeb Kamran; Muhammad Junaid Shahid; Muhammad Sheraz; Muhammad Awais; Mehtab Shabir; Muhammad Yasir; Abdul Hameed; Muhammad Asgher; Abdul Rehman; Maria Riaz; et al. (Global Ecology and Biogeography, 2025)
Aim Variation in thermal tolerances along environmental gradients is assumed to follow similar patterns across different biological scales, including within and between species, and across communities. However, this assumption has yet to be tested using comprehensive datasets collected through standardised methodologies. Location Southern Asia. Time Period 2017–2019. Major Taxa Studied Ants, beetles, grasshoppers, and spiders. Methods We quantified the associations between thermal tolerance traits and elevation or temperature at three biological scales (community, broad taxonomic group, and species) along two distinct elevational transects in Southern Asia. In total, we measured thermal tolerances of over 15,000 individuals from 114 arthropod species belonging to four invertebrate taxa (ants, beetles, grasshoppers, and spiders). We compared the relationships at each scale using mixed‐effects models. Results At the community scale, across all individuals of all species, we found a consistent decline in the values of three thermal tolerance traits (upper tolerance, lower tolerance, and tolerance breadth) with elevation along the Himalayan transect but an increase in the values of upper and lower tolerance along the Sulaiman transect. The relationships of thermal tolerance traits and elevation/temperature varied among the groups and species between the Himalayan and Sulaiman transects. This suggests that factors beyond elevation, including vegetation composition, microclimate, landscape features, and local adaptation, drive observed variation in thermal tolerance traits among and within species. Conclusion Our study highlights the interplay between thermal physiology and the environment across different habitats and biological scales. Our findings indicate that predicting biodiversity responses to environmental change based on thermal tolerance–environment relationships requires careful consideration of group‐ and species‐level variation. This is essential for improving the accuracy of climate change impact assessments on biodiversity.

Sustainable fill solutions: recycling EPS waste in shredded EPS-clayed soil composites for improved mechanical and compaction behaviour - Muhammad Haseeb; Zain Maqsood; Muhammad Baqir; Sofia Sarwar; Badee Alshameri; Waqas Hassan; Abbas Haider; Lin Wenli; Mehtab Alam; Jiren Xie; Liu Ang; Muhammad Umar (Transportation Geotechnics, 2025)

A metagenomics-based approach to understanding the transmission of healthcare-associated antimicrobial resistance in Pakistan - Muhammad Umer Asghar; Yuting Zhai; Ting Liu; Peixin Fan; Noor Ul Ain; Arsalan Haseeb Zaidi; Muhammad Tariq; Raul C. Mainar-Jaime; Kwangcheol C. Jeong (Journal of Hazardous Materials, 2025)

Achieving carbon-neutrality goals in Asian emerging economies: Role of investment in clean energy, eco-regulations, and green finance - Yaying Zhou; Muhammad Haseeb; Masooma Batool; Jihen Bousrih; Jingsha Wu (Gondwana Research, 2025)

Advanced fibrous matrix air electrode for high performance and durability in reversible solid oxide cells - Muhammad Haseeb Hassan; Jiyeoung Choi; Syeda Youmnah Batool; Rak-Hyun Song; Tak-Hyoung Lim; Jong-Eun Hong; Dong-Woo Joh; Seok-Joo Park; Young-Wan Ju; Hye-Sung Kim; Seung-Bok Lee (Chemical Engineering Journal, 2025)

Investigating the impact of air pollutants on vegetation and land surface dynamics - Li Wang; Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Dmitry E. Kucher; Aqil Tariq (Theoretical and Applied Climatology, 2025)

Retraction Note: Anti-rheumatic activity of pseudoephedrine (a substituted phenethylamine) in complete Freund’s adjuvant-induced arthritic rats by down regulating IL-1β, IL-6 and TNF-α as well as upregulating IL-4 and IL-10 - Haseeb Ahsan; Hafiz Muhammad Irfan; Alamgeer; Muhammad Shahzad; Mulazim Hussain Asim; Muhammad Akram; Muhammad Shoaib Zafar (Inflammopharmacology, 2025)

Non-small Cell Lung Cancer, Immunotherapy and the Influence of Gut Microbiome - Muhammad Faheem Raziq; Haseeb Manzoor; Masood Ur Rehman Kayani (Current Microbiology, 2025)

How Does Corporate Governance Deviance Impact Sustainability in Family Firms? A Stakeholder Perspective - Irfan Saleem; Muhammad Naeem; Muhammad Haseeb; Hao Ji; Said Al Fazari (Circular Economy and Sustainability, 2025)

Assessment of tomato germplasms for Mi-1.2-mediated resistance to Meloidogyne incognita: Integrating in-silico dynamics and bioinformatic approaches - Adil Zahoor; Zeenat Niaz; Muhammad Jabran; Hira Anwar; Amjad Abbas; Abdul Haseeb; Ghulam Mustafa; Sungmi Sun; Seung Hwan Yang; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2025)

Green-engineered calcium-doped carbon nanospheres enhance salt tolerance and growth in maize by modulating gene expressions and antioxidant defense mechanisms - Muhammad Haseeb Javaid; Bahar Ali; Asifa Neelam; Syed Asad Hussain Bukhari; Raheel Munir; Zulqarnain Haider; Muhammad Rehman; Hafiza Arooj Razzaq; Abdul Majeed; Yinbo Gan (Journal of Environmental Chemical Engineering, 2025)

Chlorophyll fluorescence: a smart tool for maize improvement - Muhammad Faheem Jan; Ming Li; Waqas Liaqat; Muhammad Tanveer Altaf; Changzhuang Liu; Haseeb Ahmad; Ehtisham Hassan Khan; Zain Ali; Celaleddin Barutçular; Heba I. Mohamed (Cereal Research Communications, 2025)

Investigating the Role of Gibberellic Acid in Fruit Drop Mitigation and Fruit Quality Improvement in Date Palm Cultivars - Hammad Hussain; Yue Yu; Abdul Haseeb Ahmed; Faisal Hayat; Muhammad Awais; Abdullah Ma’Arij; Guo Wei; Rashad Qadri (Applied Fruit Science, 2025)

Multiscale drought assessment with analyzing agricultural, meteorological, and hydrological impacts multi-index approaches (1991–2021) - Mingwu Zhou; Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Hania Arif; M. Abdullah-Al-Wadud; Aqil Tariq (Theoretical and Applied Climatology, 2025)

Enhancing food security: machine learning-based wheat yield prediction using remote sensing and climate data in Pakistan - Nadeem Ahmed; Syed Amer Mahmood; Muhammad Haseeb; Zainab Tahir; Saira Batool (Theoretical and Applied Climatology, 2025)

UBEM-SER: Role of sufficiency, efficiency and renewable in the decarbonization of commercial building stock at city scale - Usama Perwez; Muhammad Haseeb Rasool; Imran Aziz; Usman Zia (Sustainable Cities and Society, 2025)

Melatonin mitigates nickel oxide nanoparticles induced phytotoxicity in soybean by reducing metal accumulation, enhancing antioxidant defense and promoting nitrogen assimilation - Kashif Khan; Rayyan Khan; Zhuo Liu; Shahid Ali; Muhammad Asad Naseer; Muhammad Ali Shah; Haseeb Ahmad; Xun Bo Zhou (Journal of Hazardous Materials, 2025)

A comprehensive review on phytochemistry, pharmacology, preclinical, and clinical trials of Cydonia oblonga - Tuba; Muhammad Ajaz Hussain; Gulzar Muhammad; Muhammad Arshad Raza; Adnan Ashraf; Muhammad Tahir Haseeb; Muhammad Mushtaq; Zahid Shafiq (Phytochemistry Reviews, 2025)

Nutraceutical Impact of Pumpkin Seed Oil on Expression Levels of EZH-2 and KRT-14 Genes against DSS-induced Inflammatory Bowel Disease in the Rat Model - Asma Mukhtar; Imran Mukhtar; Humaira Muzaffar; Muhammad Naeem Faisal; Kashif ur rehman khan; Laaraib Nawaz; Muhammad Umar Ijaz; Sana Maryam; Muhammad Umair; Haseeb Anwar; Farid S. Ataya; Gaber El-Saber Batiha; et al. (Cell Biochemistry and Biophysics, 2025)
Inflammatory bowel disease is a collection of intestinal disorders that cause inflammation in the digestive tract. Prolonged inflammation in the gastrointestinal tract is a major risk factor for colorectal cancer. The objective of this study was to fucus on gene expression levels of ( KRT-14 ; associated with epithelial cell integrity) and enhancer of zeste homolog-1 ( EZH-2; involved in cellular proliferation) in a IBD rat model in order to rule out impact of nutraceuticals (pumpkin seed oil; PSO) as a complementary approach to conventional treatments of IBD. In the current study, IBD was induced using dextran sodium sulfate (DSS). Following acclimatization, rats were separated into three groups: the negative control, the positive control, and the treatment group. The DSS (1 ml/kg bw) was given to the positive control and treatment groups. Negative control was given only a normal diet. Pumpkin seed oil (PSO) was given orally as a treatment (0.5 ml/kg bw). Blood and colon tissue were obtained on the 5 th , 10 th , 14 th, and 18 th days. Physical parameters, hematology, biochemical assays, gene expression, and histopathology were carried out. After statistical analyses, macroscopic parameters showed significant differences. Biochemical analyses revealed a significant ( P ≤ 0.05) decrease in serum potassium concentrations, total cholesterol, triglycerides, total proteins, total oxidants status, and C-reactive proteins in PSO treated group as compared with positive control. Gene expression levels of KRT-14 and EZH2 were significantly ( P ≤ 0.05) upregulated in PSO treated group as compared to positive control group. Histopathology revealed that pumpkin seed oil preserved the structural integrity of colon.

Effect of tire pyrolysis oil and graphene oxide nanoparticles as an additive in the diesel engine - Haseeb Yaqoob; Hafiz Muhammad Ali (Environmental Science and Pollution Research, 2025)

Titanium dioxide nanoparticles seed priming as a remedy for nickel-induced stress in maize through antioxidant enhancement and ultrastructural optimization - Muhammad Rehman; Abdul Salam; Bahar Ali; Irshan Ahmad; Muhammad Haseeb Javaid; Zulqarnain Haider; Raheel Munir; Muhammad Umair Yasin; Imran Ali; Chunyan Yang; Sajid Muhammad; Yinbo Gan (Journal of Environmental Management, 2025)

Retraction Note: Protective effect of myricetin on nonylphenol-induced testicular toxicity: biochemical, steroidogenic, hormonal, spermatogenic, and histological-based evidences - Muhammad Umar Ijaz; Haseeb Anwar; Shabnoor Iqbal; Hammad Ismail; Asma Ashraf; Shama Mustafa; Abdul Samad (Environmental Science and Pollution Research, 2024)

Spatial distribution of groundwater quality and risk indices evaluation via consumption - Said Muhammad; Rizwan Ullah; Sehrish Amin; Haseeb Haroon; Ashfaq Ahmad (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Bioderived carbon quantum dots boost maize growth and photosynthesis by augmenting UV spectrum absorption and carbon assimilation regulatory genes - Zulqarnain Haider; Chunyan Yang; Irshan Ahmad; Samta Zia; Muhammad Haseeb Javaid; Muhammad Rehman; Muhammad Umair Yasin; Bahar Ali; Chen Nana; Yinbo Gan (Journal of Environmental Chemical Engineering, 2024)

Polygonum bistorta Linn. as a green source for synthesis of biocompatible selenium nanoparticles with potent antimicrobial and antioxidant properties - Hafiz Abdul Haseeb; Muhammad Aslam Khan; Hassam Rasheed; Muhammad Usman Zahid; Thu Dung Doan; Muhammad Aamir Ramzan Siddique; Uzair Ahmad; Syed Ali Imran Bokhari (BioMetals, 2024)

Sustainable development goals and green human resource management: A comprehensive review of environmental performance - Abdul Haseeb Tahir; Muhammad Umer; Shazia Nauman; Kashif Abbass; Huaming Song (Journal of Environmental Management, 2024)

A comprehensive review of plant-based mucilages as promising candidates for water remediation - Sehar Javed; Zarfishan Zulfiqar; Zain Fatima; Gulzar Muhammad; Muhammad Ajaz Hussain; Muhammad Mushtaq; Muhammad Tahir Haseeb (Journal of Environmental Chemical Engineering, 2024)

Comparative analysis of machine learning models for predicting PM2.5 concentrations using meteorological and chemical indicators - Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Hania Arif; Khalid F. Almutairi; Walid Soufan; Aqil Tariq (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Perusing sustainable development through education: evidence from Malaysia, Indonesia and Pakistan - Farah Khan; Muhammad Adnan Khan; Haseeb Ur Rahman (Environment, Development and Sustainability, 2024)

Effects of Withania somnifera (L.) Dunal in acute pulmonary pathophysiology in a rat model of smoke-induced lung injury and role of IRS-1 and SOX-2 - Sana Saleem; Imran Mukhtar; Hanan Y. Aati; Humaira Muzaffar; Haseeb Anwar; Musaddique Hussain; Maqsood Ahmad; Muhammad Umair; Kashif-ur-Rehman Khan (South African Journal of Botany, 2024)

Gene expression programming-based multivariate model for earth infrastructure: predicting ultimate bearing capacity of rock socketed shafts in layered soil-rock strata - Muhammad Naqeeb Nawaz; Muhammad Haseeb; Sana Ullah Qamar; Waqas Hassan; Arfan Shahzad (Modeling Earth Systems and Environment, 2024)

Green-synthesized lignin nanoparticles enhance Zea mays resilience to salt stress by improving antioxidant metabolism and mitigating ultrastructural damage - Muhammad Haseeb Javaid; Nana Chen; Muhammad Umair Yasin; Xingming Fan; Asifa Neelam; Muhammad Rehman; Zulqarnain Haider; Syed Asad Hussain Bukhari; Raheel Munir; Irshan Ahmad; Yinbo Gan (Chemosphere, 2024)

Classification of aerosol types in mega-city of Lahore (Pakistan) using ground-based remote sensing - Muhammad Nabeel Khan; Salman Tariq; Nimra Ehsan; Tunjeena Haseeb (Air Quality, Atmosphere & Health, 2024)

Techno-economic and performance assessment of a hybrid fuel cell-based combined heat and power system for dairy industry - Kashif Najeeb; Abdul Haseeb Tariq; Muhammad Hassan; Mustafa Anwar; Ali Bahadar; Syed Ali Abbas Kazmi; Muhammad Yousif (Environment, Development and Sustainability, 2024)

Assessing green energy production and industrial excellence in Asian emerging economies in the context of industrial transformation and sustainable development - Muhammad Qamar Rasheed; Zhao Yuhuan; Abdul Haseeb; Zahoor Ahmed; Shah Saud (Environment, Development and Sustainability, 2024)

Impact of spray drying operating conditions on yield, secondary metabolites, antioxidant potential and storage quality of grape (Vitis vinifera L.) pomace powder - Aurbab Shoukat; Muhammad Imran; Muhammad Kamran Khan; Muhammad Haseeb Ahmad; Rabia Shabir Ahmad; Mohamed Fawzy Ramadan; Muhammad Nadeem; Adeela Yasmin; Muhammad Abdul Rahim; Muhammad Imran Khan (South African Journal of Botany, 2024)

The synergistic potential of biochar and nanoparticles in phytoremediation and enhancing cadmium tolerance in plants - Muhammad Umair Yasin; Zulqarnain Haider; Raheel Munir; Usman Zulfiqar; Muhammad Rehman; Muhammad Haseeb Javaid; Irshan Ahmad; Chen Nana; Muhammad Sulaman Saeed; Bahar Ali; Yinbo Gan (Chemosphere, 2024)

Information communication technology, economic growth, natural resources, and renewable energy production: Evaluating the asymmetric and symmetric impacts of artificial intelligence in robotics and innovative economies - Muhammad Qamar Rasheed; Zhao Yuhuan; Zahoor Ahmed; Abdul Haseeb; Shah Saud (Journal of Cleaner Production, 2024)

Retraction Note: The role of monetary and fiscal policies in determining environmental pollution: Revisiting the N-shaped EKC hypothesis for China - Tang Zhengxia; Mohammad Haseeb; Muhammad Usman; Mohd Shuaib; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2024)

Sorghum: a Star Crop to Combat Abiotic Stresses, Food Insecurity, and Hunger Under a Changing Climate: a Review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Heba I. Mohamed; Haseeb Ahmad; Muhammad Faheem Jan; Ehtisham Hassan Khan (Journal of Soil Science and Plant Nutrition, 2024)

Sustainability analysis of neat waste tire oil powered diesel engine: A thermodynamics approach - Haseeb Yaqoob; Hafiz Muhammad Ali (Process Safety and Environmental Protection, 2024)

Towards the vision of going green in South Asian region: The role of technological innovations, renewable energy and natural resources in ecological footprint during globalization mode - Lingli Qing; Muhammad Usman; Magdalena Radulescu; Mohammad Haseeb (Resources Policy, 2024)

Spatial soil loss prediction impacted by long-term land use/land cover change: a case study of Swat District - Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Saira Batool; Muhammad Umar Farooq (Environmental Monitoring and Assessment, 2024)

Can sustainable resource management overcome geopolitical risk? - Adnan Safi; Muhammad Haseeb; Madeeha Islam; Muhammad Umar (Resources Policy, 2023)

Impact of different proportions of sweet potato (Ipomoea batatas L.) flour on physical, chemical and sensory parameters of straight grade flour-based cake rusk - Hafiza Saher Rafique; Ashiq Hussain; Muhammad Nadeem; Abdul Rehman; Tahira Siddique; Ayesha Najam; Haseeb Haroon; Muhammad Rehan Arif; Shazia Yaqub; Haya Fatima; Salah Laaraj (Food and Humanity, 2023)

Performance and emissions characteristics of tire pyrolysis oil in diesel engine: an experimental investigation - Haseeb Yaqoob; Hafiz Muhammad Ali; Haider Abbas; Osama Abid; Muhammad Ahmad Jamil; Talha Ahmed (Clean Technologies and Environmental Policy, 2023)

Nexuses between carbon emissions, trade openness, transport services, globalization index, and growth in China: targeting the sustainable development goals - Li Huang; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Abdul Haseeb; Muhammad Bashir Khan; Amir Rafique (Environmental Science and Pollution Research, 2023)

Experimental assessment of retrofitted damaged mortarless dry stacked interlocking masonry walls - Saeed Akbar; Akhtar Gul; Inayat Ullah Khan; Muhammad Haseeb; Khan Shahzada; Sajjad Wali Khan; Naveed Ahmad (Soil Dynamics and Earthquake Engineering, 2023)

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

Assessing Household’s Municipal Waste Segregation Intentions in Metropolitan Cities of Pakistan: A Structural Equation Modeling Approach - Tanzila Akmal; Faisal Jamil; Muhammad Haseeb Raza; Cosimo Magazzino; Babar Hussain (Environmental Monitoring and Assessment, 2023)
There is a growing concern about inappropriate waste disposal and its negative impact on human health and the environment. The objective of this study is to understand household waste segregation intention considering psychological, institutional, and situational factors simultaneously. Insights into the motivations of household waste segregation drivers may assist in a better knowledge of how to pursue the most efficient and effective initiatives. For this purpose, data from a representative sample comprising 849 households is obtained from the twin cities of Islamabad and Rawalpindi (Pakistan). The empirical analysis employs a Structural Equation Modeling (SEM) approach, showing that policy instruments have significant direct and indirect impacts on households’ segregation intentions. The results highlight that government policy instruments strengthen personal and perceived norms for waste segregation intentions, resulting in an external intervention that would encourage intrinsic motivation. Therefore, policy actions become the main entry point for initiating waste segregation behavior. Public policy must continue to emphasize waste segregation since it may help resource recovery. This is imperative because the environment is a shared resource, and its conservation increases social welfare.

Exploring the multifunctional roles of quantum dots for unlocking the future of biology and medicine - Muhammad Kashif Ali; Saher Javaid; Haseeb Afzal; Imran Zafar; Kompal Fayyaz; Qurat ul Ain; Mohd Ashraf Rather; Md. Jamal Hossain; Summya Rashid; Khalid Ali Khan; Rohit Sharma (Environmental Research, 2023)

Green supply chain management and firm sustainable performance: The awareness of China Pakistan Economic Corridor - Haseeb Ur Rahman; Muhammad Zahid; Mehran Ullah; Mamdouh Abdulaziz Saleh Al-Faryan (Journal of Cleaner Production, 2023)

Quantifying irrigation water demand and supply gap using remote sensing and GIS in Multan, Pakistan - Muhammad Haseeb; Hafiz Umar Farid; Zahid Mahmood Khan; Muhammad Naveed Anjum; Akhlaq Ahmad; Muhammad Mubeen (Environmental Monitoring and Assessment, 2023)

RETRACTED ARTICLE: The role of monetary and fiscal policies in determining environmental pollution: Revisiting the N-shaped EKC hypothesis for China - Tang Zhengxia; Mohammad Haseeb; Muhammad Usman; Mohd Shuaib; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2023)

Impact of green human resource management on green creativity in pharmaceutical companies: mediation role of green mindset - Muhammad Haseeb Shakil; Rana Nadir Idrees; Sadaf Ehsan; Waseem Anwar (Environmental Science and Pollution Research, 2023)

Attenuative effect of astilbin on polystyrene microplastics induced testicular damage: Biochemical, spermatological and histopathological-based evidences - Arooj Rizwan; Muhammad Umar Ijaz; Ali Hamza; Haseeb Anwar (Toxicology and Applied Pharmacology, 2023)

Dyeing of wool fabric with natural dye extracted from Dalbergia Sissoo using natural mordants - Kashif Iqbal; Haseeb Afzal; Muhammad Owais Raza Siddiqui; Uzma Bashir; Khayale Jan; Amir Abbas; Hafiz Affan Abid (Sustainable Chemistry and Pharmacy, 2023)

Islamic corporate sustainability practices index aligned with SDGs towards better financial performance: Evidence from the Malaysian and Indonesian Islamic banking industry - Amin Jan; Haseeb Ur Rahman; Muhammad Zahid; Anas A. Salameh; Parvez Alam Khan; Mamdouh Abdulaziz Saleh Al-Faryan; Roslizawati Binti Che Aziz; H. Elhosiny Ali (Journal of Cleaner Production, 2023)

ESG and firm performance: The rarely explored moderation of sustainability strategy and top management commitment - Haseeb Ur Rahman; Muhammad Zahid; Mamdouh Abdulaziz Saleh Al-Faryan (Journal of Cleaner Production, 2023)

Do demographic factors affect the environment? Empirical evidence from the Middle East and North African countries - Ilham Haouas; Muhammad Haseeb; Muhammad Azam; Zia Ur Rehman (Environmental Science and Pollution Research, 2023)

Impact of technology on the relation between disaggregated energy consumption and CO2 emission in populous countries of Asia - Tang Zhengxia; Zakia Batool; Sajjad Ali; Mohammad Haseeb; Vipin Jain; Syed Muhammad Faraz Raza; Prasun Chakrabarti (Environmental Science and Pollution Research, 2023)

Therapeutic effect of gossypetin against paraquat-induced testicular damage in male rats: a histological and biochemical study - Shama Mustafa; Haseeb Anwar; Qurat ul Ain; Hussain Ahmed; Shabnoor Iqbal; Muhammad Umar Ijaz (Environmental Science and Pollution Research, 2023)

Metal pollution and potential human health risk assessment in major seafood items (fish, crustaceans, and cephalopods) - Muhammad Haseeb-ur-Rehman; Alia Bano Munshi; Usman Atique; Shahida Kalsoom (Marine Pollution Bulletin, 2023)

Articulating natural resource abundance, economic complexity, education and environmental sustainability in MENA countries: Evidence from advanced panel estimation - Shah Saud; Abdul Haseeb; Muhammad Wasif Zafar; Huiyun Li (Resources Policy, 2023)

Recent Advances and Treatment of Emerging Contaminants Through the Bio-assisted Method: A Comprehensive Review - Abdul Sattar Jatoi; Jawad Ahmed; Faheem Akhter; Syed Haseeb Sultan; Ghulam Sever Chandio; Shoaib Ahmed; Zubair Hashmi; Muhammad Azam Usto; Muhammad Shuaib Shaikh; Muhammad Siddique; Ghulamullah Maitlo (Water, Air, & Soil Pollution, 2023)

Coupling biochar with microbial inoculants improves maize growth and nutrients acquisition under phosphorous-limited soil - Hafiz Muhammad Rashad Javeed; Rimsha Naeem; Mazhar Ali; Rafi Qamar; Muhammad Aqeel Sarwar; Fahim Nawaz; Atique-ur-Rehman; Muhammad Shehzad; Amjad Farooq; Haseeb-ur-Rehman; Samina Khalid; Khuram Mubeen; et al. (Acta Physiologiae Plantarum, 2022)

Robust segmentation of underwater fish based on multi-level feature accumulation - Adnan Haider; Muhammad Arsalan; Jiho Choi; Haseeb Sultan; Kang Ryoung Park (Frontiers in Marine Science, 2022)
Because fish are vital to marine ecosystems, monitoring and accurate detection are crucial for assessing the potential for fisheries in these environments. Conventionally, fish-related assessment is conducted manually, which makes it labor-intensive and time-consuming. In addition, the assessments are challenging owing to underwater visibility limitations, which leads to poor detection accuracy. To overcome these problems, we propose two novel architectures for the automatic and high-performance segmentation of fish populations. In this study, the efficient fish segmentation network (EFS-Net) and multi-level feature accumulation-based segmentation network (MFAS-Net) are the base and final networks, respectively. In deep convolutional neural networks, the initial layers usually contain potential spatial information. Therefore, the EFS-Net employs a series of convolution layers in the early stage of the network for optimal feature extraction. To boost segmentation accuracy, the MFAS-Net uses an initial feature refinement and transfer block to refine potential low-level information and subsequently transfers it to the deep stages of the network. Moreover, the MFAS-Net employs multi-level feature accumulation that improves pixel-wise prediction for fish that are indistinct. The proposed networks are evaluated using two publicly available datasets, namely DeepFish and semantic segmentation of underwater imagery (SUIM), both of which contain challenging underwater fish segmentation images. The experimental results reveal that mean intersection-over-unions of 76.42% and 92.0% are attained by the proposed method for the DeepFish and SUIM datasets, respectively; these values are higher than those by the state-of-the-art methods such as A-LCFCN+PM and DPANet. In addition, high segmentation performance is achieved without compromising the computational efficiency of the networks. The MFAS-Net requires only 3.57 million trainable parameters to be fully trained. The proposed model and the complete code will be made available 1 .

Do environmental technology and banking sector development matter for green growth? Evidence from top-polluted economies - Manzoor Ahmed; Muhammad Hafeez; Muhammad Abdul Kaium; Sana Ullah; Haseeb Ahmad (Environmental Science and Pollution Research, 2022)

Tumor necrosis factor-alpha, prostaglandin-E2 and interleukin-1β targeted anti-arthritic potential of fluvoxamine: drug repurposing - Haseeb Ahsan; Mahnoor Ayub; Hafiz Muhammad Irfan; Muhammad Saleem; Irfan Anjum; Ihtisham Haider; Awais Asif; Syed Qamar Abbas; Syed Shams ul Hulassan (Environmental Science and Pollution Research, 2022)

Extracellular vesicles and exosome: insight from physiological regulatory perspectives - Muhammad Yasir Waqas; Muhammad Arshad Javid; Muhammad Mudasser Nazir; Nasir Niaz; Muhammad Farrukh Nisar; Zahid Manzoor; Sheraz Ahmed Bhatti; Sajid Hameed; Muhammad Haseeb Khaliq (Journal of Physiology and Biochemistry, 2022)

Impact of spatial and temporal changes in climate on the Kunhar River Watershed, Pakistan - Ghulam Nabi; Muhammad Tayyab; Haseeb Akbar; Muhammad Arfan; Ijaz Ahmad; Muhammad Masood; Aqeela Zahra (Arabian Journal of Geosciences, 2022)

Spectroscopic techniques for monitoring changes in the quality of milk and other dairy products during processing and storage - Mohammed Loudiyi; Havva Tümay Temiz; Amna Sahar; Muhammad Haseeb Ahmad; Oumayma Boukria; Abdo Hassoun; Abderrahmane Aït-Kaddour (Critical Reviews in Food Science and Nutrition, 2022)

Recent approaches on the optimization of biomass gasification process parameters for product H2 and syngas ratio: a review - Muhammad Zain Siddiqui; Mahshab Sheraz; Umair Ali Toor; Ali Anus; Abid Mahmood; Muhammad Haseeb; Muhammad Ibrahim; Kuan Shiong Khoo; Vishno Vardhan Devadas; Muhammad Mubashir; Sami Ullah; Pau Loke Show (Environment, Development and Sustainability, 2022)

The long-run relationship between energy consumption, oil prices, and carbon dioxide emissions in European countries - Muhammad Qamar Rasheed; Abdul Haseeb; Tomiwa Sunday Adebayo; Zahoor Ahmed; Mahmood Ahmad (Environmental Science and Pollution Research, 2022)

A controversy on the three fundamental growth determinants in selected CEE countries - Hui-Yun Li; Shah Saud; Abdul Haseeb; Muhammad Wasif Zafar; Songsheng Chen; Sumayya (Environmental Science and Pollution Research, 2022)

Forecasting carbon emissions due to electricity power generation in Bahrain - Mohammed Redha Qader; Shahnawaz Khan; Mustafa Kamal; Muhammad Usman; Mohammad Haseeb (Environmental Science and Pollution Research, 2022)

Connecting integrated management system with corporate sustainability and firm performance: from the Malaysian real estate and construction industry perspective - Haseeb Ur Rahman; Muhammad Zahid; Ali Muhammad (Environment, Development and Sustainability, 2022)

Genome-wide identification and characterization of a plant-specific Dof transcription factor gene family in olive (Olea europaea) and its comparison with Arabidopsis - Mariyam; Muhammad Shafiq; Muhammad Haseeb; Rana Muhammad Atif; Syed Agha Armaghan Asad Abbas Naqvi; Numan Ali; Muhammad Arshad Javed; Fizza Gillani; Muhammad Saleem Haider (Horticulture, Environment, and Biotechnology, 2021)

A New Sequential Forward Feature Selection (SFFS) Algorithm for Mining Best Topological and Biological Features to Predict Protein Complexes from Protein–Protein Interaction Networks (PPINs) - Haseeb Younis; Muhammad Waqas Anwar; Muhammad Usman Ghani Khan; Aisha Sikandar; Usama Ijaz Bajwa (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Adoption of green banking practices and environmental performance in Pakistan: a demonstration of structural equation modelling - Alam Rehman; Irfan Ullah; Fakhr-e-Alam Afridi; Zain Ullah; Muhammad Zeeshan; Arif Hussain; Haseeb Ur Rahman (Environment, Development and Sustainability, 2021)

RETRACTED ARTICLE: Pharmacological support to anti-arthritic prospective of physostigmine: a new approach - Haseeb Ahsan; Ihtisham Haider; Muhammad Naveed Mushtaq; Muhammad Naeem Qaisar; Farwa Naqvi; Awais Asif (Inflammopharmacology, 2021)

Do risk perceptions and constraints influence the adoption of climate change practices among small livestock herders in Punjab, Pakistan? - Muhammad Faisal; Xia Chunping; Azhar Abbas; Muhammad Haseeb Raza; Shoaib Akhtar; Muhammad Arslan Ajmal; Abdelrahman Ali (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Anti-rheumatic activity of pseudoephedrine (a substituted phenethylamine) in complete Freund’s adjuvant-induced arthritic rats by down regulating IL-1β, IL-6 and TNF-α as well as upregulating IL-4 and IL-10 - Haseeb Ahsan; Hafiz Muhammad Irfan; Alamgeer; Muhammad Shahzad; Mulazim Hussain Asim; Muhammad Akram; Muhammad Shoaib Zafar (Inflammopharmacology, 2021)

Metataxonomic analysis of microbiota from Pakistani dromedary camelids milk and characterization of a newly isolated Lactobacillus fermentum strain with probiotic and bio-yogurt starter traits - Kanwal Aziz; Zubair Farooq; Muhammad Tariq; Arsalan Haseeb Zaidi (Folia Microbiologica, 2021)

Does the adaptation of climate-smart agricultural practices increase farmers’ resilience to climate change? - Ihsan Jamil; Wen Jun; Bushra Mughal; Muhammad Haseeb Raza; Muhammad Ali Imran; Ali Waheed (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Protective effect of myricetin on nonylphenol-induced testicular toxicity: biochemical, steroidogenic, hormonal, spermatogenic, and histological-based evidences - Muhammad Umar Ijaz; Haseeb Anwar; Shabnoor Iqbal; Hammad Ismail; Asma Ashraf; Shama Mustafa; Abdul Samad (Environmental Science and Pollution Research, 2021)

Dynamic nexus among tourism, corruption, democracy and environmental degradation: a panel data investigation - Muhammad Haseeb; Muhammad Azam (Environment, Development and Sustainability, 2021)

The role of technology innovation and people’s connectivity in testing environmental Kuznets curve and pollution heaven hypotheses across the Belt and Road host countries: new evidence from Method of Moments Quantile Regression - Hui An; Asif Razzaq; Muhammad Haseeb; Leonardus W. W. Mihardjo (Environmental Science and Pollution Research, 2021)

The dynamics effect of green technology innovation on economic growth and CO2 emission in Singapore: new evidence from bootstrap ARDL approach - Tang Meirun; Leonardus WW Mihardjo; Muhammad Haseeb; Syed Abdul Rehman Khan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2021)

Effect of Vanadium on Growth, Photosynthesis, Reactive Oxygen Species, Antioxidant Enzymes, and Cell Death of Rice - Muhammad Mohsin Altaf; Xiao-ping Diao; Atique ur Rehman; Muhammad Imtiaz; Awais Shakoor; Muhammad Ahsan Altaf; Haseeb Younis; Pengcheng Fu; Muhammad Usman Ghani (Journal of Soil Science and Plant Nutrition, 2020)

Modeling smallholder livestock herders’ intentions to adopt climate smart practices: An extended theory of planned behavior - Muhammad Faisal; Xia Chunping; Shoaib Akhtar; Muhammad Haseeb Raza; Muhammad Tariq Iqbal Khan; Muhammad Arslan Ajmal (Environmental Science and Pollution Research, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Moderating role of financial development in environmental Kuznets: a case study of Malaysia - Abid Rashid Gill; Sallahuddin Hassan; Muhammad Haseeb (Environmental Science and Pollution Research, 2019)

In vitro consumption patterns of pepper weevil, Anthonomus eugenii (Coleoptera: Curculionidae) on two commercial pepper cultivars in Florida - Pengxiang Wu; Muhammad Haseeb; Runzhi Zhang; Lambert H. B. Kanga; Jesusa C. Legaspi (Applied Entomology and Zoology, 2019)

The nexus between financial development, income level, and environment in Central and Eastern European Countries: a perspective on Belt and Road Initiative - Shah Saud; Songsheng Chen; Abdul Haseeb; Khalid Khan; Muhammad Imran (Environmental Science and Pollution Research, 2019)

Transcriptional Study Revealed That Boron Supplementation May Alter the Immune-Related Genes Through MAPK Signaling in Ostrich Chick Thymus - Ke Xiao; Keli Yang; Jing Wang; Pengpeng Sun; Haibo Huang; Haseeb Khaliq; Muhammad Ahsan Naeem; Juming Zhong; Kemei Peng (Biological Trace Element Research, 2019)

The trade-environment nexus in light of governance: a global potential - Rizwana Yasmeen; Yunong Li; Muhammad Hafeez; Haseeb Ahmad (Environmental Science and Pollution Research, 2018)

Financial development, globalization, and CO2 emission in the presence of EKC: evidence from BRICS countries - Abdul Haseeb; Enjun Xia; Danish; Muhammad Awais Baloch; Kashif Abbas (Environmental Science and Pollution Research, 2018)

Development of streamflow prediction models for a weir using ANN and step-wise regression - Muhammad Hassan; Haseeb Zaffar; Imran Mehmood; Anwar Khitab (Modeling Earth Systems and Environment, 2018)